Therapeutic Efficacy Of Hcg And Manual Pressure In The Management Of Anovulation In Cattle - Talukdar, D.J.; Nath, K.C.; Dutta , J.; Talukdar , P. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was conducted on 30 repeat breeder crossbred cows of private farms located around the college campus. The cows were equally divided into five treatment groups comprising six cows in each group. In group A, C and D the ovulation was induced by 3000 IU of hCG (Chorulon), while in group B and E the ovulation was induced by rupturing the Graafian follicle manually on 1-2 days of oestrus.The group A and B cows were examined on day 0, 2, 8, 14 and 18 of oestrus to record the changes of the genital organs after induction of ovulation. The study revealed that the occurrence of vulvar congestion, patency of cervix and uterine tone was similar in cows treated with hCG and manual pressure for induction of ovulation. The Graafian follicle was detectable in all cows on day 0 of oestrus in hCG treated group and up to 2 days in manual pressure group. The corpus haemorrhagicum was detected in 83.33 per cent cows on day 2 of oestrus in hCG treated group against 16.66 per cent in cows in manual pressure group. The mature corpus luteum was detected in all the cows on day 8 and day 14 of oestrus. The conception rates by using treatment protocol A (3000 IU hCG and AI in subsequent oestrus), protocol B (manual induction of ovulation and AI in subsequent oestrus ) and protocol C (3000 IU hCG immediately after AI) were found to be 100% in cows of repeat breeding due to anovulation. Progesterone therapy (750 mg) on day 3, 10 and 17 following AI with hCG and manual induction of ovulation improved conception rate(100 vs 83.33%) in repeat breeder cows affected with anovulation.
Keywords: Repeat breeder; anovulation; hCG; manual pressure